Increase in foot arch asymmetry after full marathon completion. Issue 21 (2nd November 2021) - Fukano, Mako; Nakagawa, Kento; Inami, Takayuki; Higashihara, Ayako; Iizuka, Satoshi; Narita, Takaya; Maemichi, Toshihiro; yoshimura, Akane; Yamaguchi, Shota; Iso, Shigeo
ABSTRACT: Long-distance running results in lowering of the foot medial longitudinal arch, but it is unknown whether the left and right arches decrease equally. This study aimed to determine whether foot arch asymmetry increases upon completion of a full marathon and to identify factors capable of explaining the degree of asymmetry of navicular height and navicular height displacement. The three-dimensional foot posture data of 74 collegiate runners were obtained using an optical foot scanner system before (PRE) and immediately after (POST) a full marathon. The navicular height and arch height ratio (normalised navicular height by foot length) of both feet significantly decreased from PRE to POST full marathon completion (44.3 ± 6.3 mm versus 40.8 ± 6.5 mm, 17.8 ± 2.5 versus 16.6 ± 2.7, respectively; p < 0.001, both). The asymmetry of the arch height ratio was significantly greater POST than PRE marathon. Multiple linear regression analysis indicated that the POST-race Asymmetry Index (AI) of navicular height was significantly predicted by the PRE-race AI of navicular height; navicular height displacement was predicted by PRE-race navicular height and the marathon time. Full marathon running induced increasing asymmetry and lowering of the medial longitudinal arch in runners.